Bibliometrics-based decision tree (BBDT) for deciding whether two universities in the Leiden ranking differ substantially in their performance - Bornmann, Lutz (Scientometrics, 2020)
Fast-and-frugal heuristics are simple judgement strategies that are based on only a few predictor variables. Bornmann and Marewski (Scientometrics 120(2):419–459, 2019) introduced bibliometrics-based heuristics (BBHs) which are judgement strategies in evaluative bibliometrics being solely based on publication and/or citation data. To support the understanding and applying of BBHs, Bornmann (in press) proposed bibliometrics-based decision trees (BBDTs) that are visualized BBHs. In this letter to the editor, a BBDT is presented that can be used for the interpretation of results from the Leiden ranking.